Analisis Karakteristik Daerah Aliran Sungai (DAS) Dodokan dan Dampak Perubahan Penggunaan Lahan terhadap Kejadian Banjir - Muhammad Rafi; Andani Rahman; Puja Setiawati (Trends Research of Environmental Studies, 2025)
The Dodokan Watershed (DAS Dodokan) plays an important role in maintaining the hydrological balance of the surrounding region. However, land use changes that have occurred over the past few decades have the potential to affect hydrological characteristics and increase the risk of flooding. This study aims to analyze the characteristics of the Dodokan Watershed and assess the impact of land use change on flood events. The methods used include spatial analysis with remote sensing imagery and Geographic Information Systems (GIS) to identify patterns of land cover change, as well as hydrological analysis using watershed morphometric parameters. Rainfall data, slope gradient, and soil types were also analyzed to strengthen interpretation. The results show a significant conversion of forest areas into residential land and intensive agriculture. These changes have reduced soil infiltration capacity, increased surface runoff, and decreased the natural storage capacity of the watershed. Hydrological analysis indicates an increase in runoff coefficients and peak flood discharge during certain periods. This condition demonstrates that land use change contributes substantially to the rising frequency and intensity of floods in the Dodokan Watershed. These findings highlight the need for sustainable watershed management strategies through forest conservation, rehabilitation of critical land, and the implementation of environmentally friendly spatial planning to minimize future flood risks.